Forest conservation in protected areas of Bangladesh Policy and community development perspectives - Chowdhury, Mohammad Shaheed Hossain (World Forests,, 2014)
This book is dealing with a number of issues under the broad subject matter of protected area focusing on the policy of collaborative management as a means to augment the forest conservation activities and enhance community development in Bangladesh. Comprehending the malfunction of traditional forest management in Bangladesh, the government explored and implemented few alternative strategies for better management of the country's forest resources. Establishing protected areas was the first initiative of such strategy. But simple declaration of protected areas has not functionally worked in the prevention of forest degradation. Because, local communities face hardships after a forest is notified as protected area. This is mainly due to the imposing of strict regulations that curb the flow of forest resources for their livelihoods. Therefore, considering the pragmatism, the government started collaborative management approach with the active participation of local communities in five protected areas as pilot projects. Studies on the pilot sites, covered in the book emerged with the success stories of protected area co-management, both in terms of community development and biodiversity conservation. Significant level of development was noticed in the socio-economic conditions of the surrounding communities as an impact of this new strategy. Empowerment and improved social dignity of women participants signifies the initiation of co-management approach. The principles of participatory governance were found reasonably well reflected in legal and policy frameworks. Based on the lessons from the studies, a general metaphysical model, namely 'Spider-web model of protected area co-management' has been developed that can be potentially applicable in countries where local communities rely heavily on protected areas. We hope that the contents of the book provide useful information for policy makers developing more comprehensive programs for protected area management in Bangladesh.